Recent Progress in Layered Double Hydroxides-based Materials as Sustainable Nanoadsorbents for Hazardous Pollutants Recovery from Aqueous Medium - Dib, Mustapha; Kacem, Marieme; Tajuddin, Nazrizawati A. (Current Materials Science, 2025)
The increasing prevalence of hazardous pollutants in water poses a significant global threat to the environment and human health. To address this issue, various methodologies have been developed for the determination and removal of harmful contaminants, with layered double hydroxides (LDHs)-based materials emerging as promising adsorbents. This review focuses on recent advancements in the application of LDHs-based materials for the removal of specific harmful pollutants, such as selenium, fluoride, heavy metals, and organic dyes, from aqueous solutions. Heavy metals and organic dyes, in particular, are major contributors to environmental pollution, necessitating effective and eco-friendly treatment methods.
Keywords: photocatalytic water